Financing policies of Croatian publicly listed firms - Mihaela Grubisic Seba (UTMS Journal of Economics, 2013)
Croatia is a typical bank-based transition economy whose capital market has been primarily used for secondary trading purposes since its re-establishment in 1990s. Except for a couple of exceptions, public offers of shares and corporate bonds have been rather rate. Private offerings of shares and short-term debt have been more frequent. However, due to secondary debt market illiquidity, the debt issues are signed up and either held until maturity or renewal, or they are traded exclusively between the institutional investors. This paper provides evidence from the field on financing preferences of Croatian public companies regarding seasoned equity and corporate debt issuance. It questiones why public offerings of corporate securities in non-financial sector after initial, mostly mandatory shares' listing have been rare and whether making decisions on securities' offers depend on other financial instruments' sufficiency, costs of issunace or previous experience of companies in collecting funds in the capital market.
Keywords: G1; 330; corporate financing preferences; publicly listed companies; CFOs' survey; Croatian capital market; non-financial sector; bank-based financial system